2007
DOI: 10.1089/apc.2007.0004
|View full text |Cite
|
Sign up to set email alerts
|

Stigmatization of Patients with AIDS: Understanding the Interrelationships between Thai Nurses' Attitudes toward HIV/AIDS, Drug Use, and Commercial Sex

Abstract: There is currently a scarcity of research on the nature of HIV/AIDS stigma within the Thai health context. This is problematic given the negative role of stigma in hindering the provision of patient care and treatment. This study used a mixed-method approach to investigate the interrelationships between the stigma of HIV/AIDS and the stigmas relating to its various modes of disease transmission including injection drug use (IDU). Twenty interviews were conducted with trainees and qualified nurses from a Bangko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(27 citation statements)
references
References 27 publications
4
22
0
1
Order By: Relevance
“…In our study, when the HCPs were faced with the option of treating a person living with HIV or avoiding treatment, they opted to treat. In this regard our findings were similar to the study reported by Chan (Chan, Rungpueng, and Reidpath 2009) and in contrast to studies where HCPs were suggested to have avoidant attitudes towards people with HIV (Chan and Reidpath 2007;Chan et al 2008). It can be argued that professional codes of practice should provide guidance for decisions in these matters when HCPs find themselves challenged by such a dilemma.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, when the HCPs were faced with the option of treating a person living with HIV or avoiding treatment, they opted to treat. In this regard our findings were similar to the study reported by Chan (Chan, Rungpueng, and Reidpath 2009) and in contrast to studies where HCPs were suggested to have avoidant attitudes towards people with HIV (Chan and Reidpath 2007;Chan et al 2008). It can be argued that professional codes of practice should provide guidance for decisions in these matters when HCPs find themselves challenged by such a dilemma.…”
Section: Discussionsupporting
confidence: 89%
“…While the number of people participating in this study was low (as the number of health professionals exposed to HIV or hepatitis C was low), data from this study is valuable for to two key reasons. Firstly, there is scant research being conducted on prevention, management and treatment of HIV in UAE (Barss 2009) and, secondly, almost no data exists on the experience of health professionals of such an occupational exposure (Chan and Reidpath 2007) Methods A qualitative study applying an abbreviated version of grounded theory was used to explore the effect of stigma and culture on reporting by HCPs following occupational exposure to HIV and hepatitis C (Charmaz 2006;Willig 2008). Abbreviated grounded theory is an approach to grounded theory where study data is analysed 'following the principles of grounded theory (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…21,33,68,91,93,94 Interventionists may consider incorporating opportunities for self-reflection on stigmatized behaviors frequently associated with HIV such as homosexuality, commercial sex work, and drug use as addressing layered stigmas, if present, may yield even greater changes in negative attitudes. 16,[95][96][97][98] Before interpersonal level interventions geared to PLWH and health care providers can be implemented, it is imperative that supportive structural conditions for the equal treatment of PLWH in the health care settings are in place. 99,100 This means that adequate national legislation, appropriate upto-date treatment protocols, and nondiscriminatory institutional policies are present, effectively conveyed, and easy to access for health care providers.…”
Section: Discussionmentioning
confidence: 99%
“…Goffmans definition refers to attributions about a person's value (109); which would then require some operational measure of value (112). In the area of HIV, some studies have attempted to measure this in terms of social distance (113), others have attempted to infer it on the basis of prejudicial attitudes (114). Yet another study used the experiences of PLWHA to assess the levels and effects of felt or perceived stigma (115).…”
Section: Stigmamentioning
confidence: 99%
“…Because of the impact this may have on the provision of treatment knowing the constituent effects is important. In a series of experimental studies in which medical and nursing students responded to descriptions of people with HIV, Leukaemia, or no disease, who had either visited a sex worker, been an injecting drug user, or engaged in no high risk behaviour, Chan and colleagues were able to examine the way that a complex of HIV related stigmas could be layered (113,131,132). In combination with other sources of stigma, the disease stigma of HIV itself was often less critical than the other sources of stigma.…”
Section: Stigmamentioning
confidence: 99%